The deerslayer, or, The first war-path - Cooper, James Fenimore, 1789-1851 (Cooper, James Fenimore, 1789-1851. Works. 1980., 1987)
Natty Bumppo, a young white hunter brought up in the Delaware Indian tribe, has to defend settlers before returning to the Iroquois who have allowed him parole.